Anakinra for palmoplantar pustulosis: results from a randomized, double‐blind, multicentre, two‐staged, adaptive placebo‐controlled trial (APRICOT). (12th October 2021) - Cro, S.; Cornelius, V.R.; Pink, A.E.; Wilson, R.; Pushpa‐Rajah, A.; Patel, P.; Abdul‐Wahab, A.; August, S.; Azad, J.; Becher, G.; Chapman, A.; Dunnill, G.; et al.
Summary: Background: Palmoplantar pustulosis (PPP) is a rare, debilitating, chronic inflammatory skin disease that affects the hands and feet. Clinical, immunological and genetic findings suggest a pathogenic role for interleukin (IL)‐1. Objectives: To determine whether anakinra (an IL‐1 receptor antagonist) delivers therapeutic benefit in PPP. Methods: This was a randomized (1 : 1), double‐blind, two‐staged, adaptive, UK multicentre, placebo‐controlled trial [ISCRTN13127147 (registered 1 August 2016); EudraCT number: 2015‐003600‐23 (registered 1 April 2016)]. Participants had a diagnosis of PPP (> 6 months) requiring systemic therapy. Treatment was 8 weeks of anakinra or placebo via daily, self‐administered subcutaneous injections. Primary outcome was the Palmoplantar Pustulosis Psoriasis Area and Severity Index (PPPASI) at 8 weeks. Results: A total of 374 patients were screened; 64 were enrolled (31 in the anakinra arm and 33 in the placebo arm) with a mean (SD) baseline PPPASI of 17·8 (10·5) and a PPP investigator's global assessment of severe (50%) or moderate (50%). The baseline adjusted mean difference in PPPASI favoured anakinra but did not demonstrate superiority in the intention‐to‐treat analysis [–1·65, 95% confidence interval (CI) –4·77 to 1·47; P = 0·30]. Similarly, secondary objective measures, including fresh pustule count (2·94, 95% CI –26·44 to 32·33; favouring anakinra), total pustule count (–30·08, 95% CI –83·20 to 23·05; favouring placebo) and patient‐reported outcomes, did not show superiority of anakinra. When modelling the impact of adherence, the PPPASI complier average causal effect for an individual who received ≥ 90% of the total treatment (48% in the anakinra group) was –3·80 (95% CI –10·76 to 3·16; P = 0·285). No serious adverse events occurred. Conclusions: No evidence for the superiority of anakinra was found. IL‐1 blockade is not a useful intervention for the treatment of PPP. Abstract : What is already known about this topic? Treatment options for palmoplantar pustulosis include superpotent corticosteroids, phototherapy, acitretin, methotrexate and ciclosporin. However, these have poor evidence for benefit and there is a risk of toxicity with long‐term use. Anakinra is a recombinant interleukin (IL)‐1 receptor antagonist that blocks the activity of IL‐1α and IL‐1β, two cytokines repeatedly linked to neutrophil activation and extravasation. A therapeutic benefit of anakinra has been shown in neutrophilic dermatoses and conditions that manifest with skin pustulation. What does this study add? Anakinra was not significantly superior to placebo at 8 weeks in objective investigator‐assessed and patient‐reported measures. A greater proportion of participants in the anakinra group strongly agreed that the treatment was worthwhile. The safety profile of anakinra was consistent with previous studies. This is one of the largest randomized controlled trials for this rare condition, providing important data on its natural history and change in disease severity over time. Linked Comment: S.N. Lo and J.F. Thompson. Br J Dermatol 2022; 186:205–206 . Plain language summary available online